2023
DOI: 10.24425/bpasts.2023.144585
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of surface waviness of casting patterns made using 3D printing technologies

Paweł Zmarzły,
Damian Gogolewski,
Tomasz Kozior

Abstract: The application of 3D printers significantly improves the process of producing foundry patterns in comparison to traditional methods of their production. It should be noted that the quality of the surface texture of the foundry pattern is crucial because it affects the quality of the casting mold and eventually the finished casting. In most studies, the surface texture is examined by analyzing the 2D or 3D roughness parameters. This is a certain limitation because, in the case of 3D printing, the influence of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 17 publications
0
1
0
Order By: Relevance
“…They revealed that simulations and experiments agreed satisfactorily and observed surface waviness significantly influenced by the curing temperature rather than the analyzed neat resin layer thickness. Zmarzły et al [18] discussed the influence of the advanced (3D printing layer thickness) and traditional methods on forming the waviness of the surface of casting patterns. Layer thickness significantly influences the values of waviness parameters of the surface in the casting patterns made with PJM (PolyJet Matrix), FDM (fused deposition modelling) and SLS (selective laser sintering) additive technologies.…”
mentioning
confidence: 99%
“…They revealed that simulations and experiments agreed satisfactorily and observed surface waviness significantly influenced by the curing temperature rather than the analyzed neat resin layer thickness. Zmarzły et al [18] discussed the influence of the advanced (3D printing layer thickness) and traditional methods on forming the waviness of the surface of casting patterns. Layer thickness significantly influences the values of waviness parameters of the surface in the casting patterns made with PJM (PolyJet Matrix), FDM (fused deposition modelling) and SLS (selective laser sintering) additive technologies.…”
mentioning
confidence: 99%